6ER-021 Evaluation of COVID mortality during hospital admission in patients receiving oncological treatment. (23rd March 2022) - Serramontmany Morante, E; Cardona-Pascual, I; Garcia Ortega, P; Carreras Soler, M; Gorgas Torner, MQ; Cidoncha Muñoz, I; Felip Font, E
Abstract : Background and importance: COVID-19 mortality changes depending on patients' characteristics. The literature describes similar mortality in general COVID-19 patients and those receiving cancer therapies. However, cancer treatments represent a heterogeneous group. Aim and objectives: To evaluate how different cancer treatments can affect COVID-19 mortality in patients requiring hospital admission. Material and methods: Retrospective observational analysis conducted from March 2020 to February 2021 in a tertiary hospital. Bio-demographic data (sex, age) and clinical data (type of cancer, ECOG, comorbidities) were obtained from the hospital records. All adult oncological patients admitted for COVID-19, who had received anticancer drugs at least 6 weeks prior to hospital admission, were included. Patients were classified according to type of treatment: chemotherapy, immunotherapy, hormonal therapies, or targeted-treatment. Results: Of 5633 cancer patients treated at our centre, 108 (1.9%) met the inclusion criteria and were included. 59 (54.6%) were men, median age 64 (21–96) years, 50 (46.3%) had ECOG 0 or 1. Treatment received: chemotherapy (62, 57.4%), immunotherapy (32, 29.5%), targeted-therapy (23, 21.2%), hormone therapy (3, 2.7%) or another antineoplastic agent (6, 5.55%). The most frequent comorbidities were: hypertension (50, 46.3%), dyslipidaemia (33, 30.6%) and diabetes (24, 22.2%). Half of the patients with lymphoid neoplasms (22, 20.3%) received chemotherapy (13; 59.1%) or immunotherapy (11; 50%). Of 20 (18.5%) patients with gastrointestinal, 13 (12.0%) with lung and 12 (11.1%) with head and neck cancer, respectively, 14 (70%), 9 (69.2%) and 10 (83.3%) had received chemotherapy. Mortality rate for all patients admitted to hospital with moderate-severe COVID was 10.4%, while patients included in our study had a higher mortality (n=38; 35.1%). Higher mortality was associated with immunotherapy (40.6%) and targeted-therapy (43.4%). Chemotherapy was less related with mortality (28.5%). Anti-CD20 was the mechanism of action most related with mortality (n=10; mortality: 60%). Conclusion and relevance: Although some evidence suggests that recent exposure to systemic anticancer therapy does not increase COVID-19 mortality, our results show that in a subgroup of moderate-severe hospitalised patients, cancer treatment does increase COVID-19 mortality. Immunotherapy and targeted-therapy could be more related to higher mortality rates than chemotherapy. Specifically, anti-CD20 have significantly higher mortality than other drugs. References and/or acknowledgements: Conflict of interest: No conflict of interest